DPR dan Perubahan Sosial: Peran Legislasi dalam Mendorong Kesetaraan Gender di Indonesia - Ibrohim; Muhammad Ali; Casnika (CV Rewang Rencang, 2025)
ABSTRACT This article attempts to reveal and analyze the role of the House of Representatives (DPR) in formulating and passing laws that support gender equality in Indonesia, the challenges faced by the DPR in implementing gender equality laws, and the impact of pro-gender equality legislation on social enterprises in society. This study aims to analyze the role of the DPR in formulating and passing gender equality laws in Indonesia, examine the challenges of their implementation, and assess their impact on social enterprises and communities as agents of change. Specifically, this study seeks to explore the causal relationship between legislative design and its transformational impact, and formulate data-based policy recommendations to strengthen inclusive and gender-responsive legislation. This study uses a juridical-sociological approach with qualitative methods, combining legal analysis and field studies. Data were collected through document studies, interviews, and observations, then analyzed descriptively and thematically. The research findings indicate that the House of Representatives (DPR) has taken important steps in gender equality legislation, such as the ratification of the TPKS Law, which emerged from civil society support. However, the DPR's role remains reactive, with implementation challenges including cultural resistance, limited budget, weak apparatus, and suboptimal oversight. The TPKS Law has had a positive impact on social enterprises, although policy support and regulatory understanding remain limited. Conclusion: The DPR plays a strategic but not yet optimal role in promoting gender equality legislation. Existing legislation has shown progress, but implementation, oversight, and budget support still need to be strengthened. Social enterprises have the potential to be key partners, but require more concrete and applicable supporting policies. The study recommends that the House of Representatives establish a cross-faction Gender Equality Caucus, implement data-driven participatory legislation, strengthen oversight using gender indicators, and build strong partnerships with social enterprises and civil society. Further research is recommended to focus on the implementation of the law and incentives for social enterprises to strengthen the House of Representatives' role as a real agent of social change. Keywords: Legislative Role, Gender Equality, House of Representatives and Social Change